Injective stabilization of additive functors, III. Asymptotic stabilization of the tensor product - Martsinkovsky, A.; Russell, J. (Algebra and Discrete Mathematics, 2021)
The injective stabilization of the tensor product is subjected to an iterative procedure that utilizes its bifunctor property. The limit of this procedure, called the asymptotic stabilization of the tensor product, provides a homological counterpart of Buchweitz’s asymptotic construction of stable cohomology. The resulting connected sequence of functors is isomorphic to Triulzi’s J-completion of the Tor functor. A comparison map from Vogel homology to the asymptotic stabilization of the tensor product is constructed and shown to be always epic. The category of finitely presented functors is shown to be complete and cocomplete. As a consequence, the inert injective stabilization of the tensor product with fixed variable a finitely generated module over an artin algebra is shown to be finitely presented. Its defect and consequently all right-derived functors are determined. New notions of asymptotic torsion and cotorsion are introduced and are related to each other.